Model Integrated Problem Solving Based Learning pada Perkuliahan Dasar-dasar Kimia Analitik - Indarini Dwi Pursitasari; Anna Permanasari (Universitas Negeri Malang, 2013)
Abstract: Integrated Problem Solving Based Learning Model on Foundation of Analytical Chemistry. This study was conducted to know the effects of Integrated Problem Solving Based Learning (IPSBL) model on problem solving skills and cognitive ability of pre-service teachers. The subjects of the study were 41 pre- service teachers, 21 in the experimental group and 20 in the control group. The data were collected through a test on problem solving skills, a test on cognitive ability, and a questionnaire on the students'opinions on the use of IPSBL model. The quantitative data were analyzed using t-test and one-way ANOVA, and the qualitative data were analyzed by counting the percentage. The results of the study show that the implementation of IPSBL model increased the problem solving skills and cognitive ability of the pre-service teachers . The model was also responded positively by the research subjects. Abstrak: Model Integrated Problem Solving Based learning pada Perkuliahan Dasar-dasar Kimia Analitik. Penelitian ini bertujuan menentukan pengaruh model Integrated Problem Solving Based Learning(IPSBL) terhadap peningkatan kemampuan problem solving dan kemampuan kognitif mahasiswa calon guru. Subjek penelitian terdiri dari 21 mahasiswa kelas eksperimen dan 20 mahasiswa kelas kontrol. Data dikumpulkan menggunakan tes kemampuan problem solving, tes kemampuan kognitif, dan angket untuk menjaring pendapat mahasiswa terhadap penggunaan model IPSBL . Data kuantitatif dianalisis denga n uji- t dan Anava dengan bantuan program SPSS 16.0. Data kualitatif dihitung persentasenya. Hasil penelitian menunjukkan bahwa model IPSBL dapat meningkatkan kemampuan problem solving dan kemampuan kognitif serta mendapat tanggapan yang positif dari mahasiswa.